The consequences of mechanised harvesting on commercial forest soils - Talent Buthelezi (22646618) (2025)
This dataset comprises the selected physical properties of soil data used to reach conclusions. This includes Pre- and Post-Harvest Soil Physical Properties: bulk density and porosity values, penetration resistance: In-situ measurements at 5 cm and 10 cm depths, site characteristics: Associated data on soil type (Hydromorphic vs. Red and Yellow Apedal) and slope gradient for each sample point. This study employed an experimental design to assess the impact of fully mechanised harvesting on the physical properties of two distinct forest soil types: well-drained Red and Yellow Apedal soils and saturated Hydromorphic soils. The study was conducted within two adjacent 15-year-old Pinus elliottii plantations established on these respective soil types. A probability-based sampling procedure, combining systematic and random techniques, was implemented to lay out the experiment. A network of 12 transects (extraction routes) was established systematically every 24 meters across the slope. Along these transects, sampling points were positioned at 24-meter intervals to capture data from machine trails. This design was consistently applied to both soil compartments to minimize the influence of natural variation. Soil data was collected in two phases: Pre-harvesting: Baseline measurements were taken in autumn. Post-harvesting: Measurements were repeated in winter on the machine trails within the same compartments. At each sampling point, both in situ and laboratory measurements were taken at depths of 5 cm and 10 cm: 1. Penetration Resistance: Measured directly in the field using a handheld penetrometer (Agratrtronix soil compaction tester model that determines the extent of subsurface soil compaction). The profile values were utilised as: 150 kPa (soft tilled layer), 200 kPa (softer soil below the hardpan), and 390 kPa (a sharp increase indicating a compacted later) 2. Bulk Density & Porosity: Undisturbed soil cores were collected using a cone sampler, transported to the laboratory, and analysed via the standard oven-drying method. Particle density was assumed at 2.65 g/cm³ for porosity calculations. The collected data was analysed using a Repeated Measures ANOVA (RMANOVA). The experimental design was a factorial model, treating soil type, depth, and slope as independent factors, and the soil physical properties as dependent variables. This approach allowed for a robust statistical examination of the significant effects of mechanized harvesting, both within and between the different soil subjects, and their interactions. Data normality was confirmed via QQ plots and histograms prior to analysis.